Spatial patterns in recent forest growth trends across the Czech Republic - Daniela Machová; Jakub Kašpar; Tomáš Kolář; Michal Rybníček; Miroslav Svoboda; Pavel Šamonil; Václav Treml; Jan Tumajer; Ivana Vašíčková; Monika Vejpustková; Lukáš Brůha (Journal of Maps)
The radial growth of trees significantly contributes to climate change mitigation by sequestering carbon into woody biomass. Radial growth trends observed in European temperate forests during the recent period of climate warming vary between growth acceleration due to longer growing seasons and growth declines due to amplified drought stress. Assessing the spatial variation of growth trends is challenging due to the point relevance of available empirical data including forest inventories and tree-ring width chronologies. Here, we used a database of tree-ring width chronologies from 596 sites and spatial models to describe the growth trends of five tree species across the Czech Republic between 1990 and 2018. The resulting map highlights multiple sources of variation in growth trends including differences between species and prominent spatial gradients along elevation, latitude, and longitude. The knowledge of spatially explicit growth trends is essential for the adaptation of the forestry sector to ongoing climate change.